2021
DOI: 10.1200/jco.2021.39.15_suppl.1012
|View full text |Cite
|
Sign up to set email alerts
|

PALOMAGE, a French real-world cohort of elderly women beyond age 70 with advanced breast cancer receiving palbociclib: Baseline characteristics and safety evaluation.

Abstract: 1012 Background: Advanced breast cancer (ABC) is common in older patients, resulting from the high incidence of breast cancer beyond age 70. This population is often limited in clinical trials. Endocrine therapy (ET) combined with a CDK4/6 inhibitor is the standard of care in ABC overexpressing hormonal receptors (HR+). Data specific to older patients are scarce in the literature, deserving further research. Methods: PALOMAGE is an ongoing French prospective study evaluating palbociclib (PAL) + ET in real lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…A more recent US study of the rates of hospitalisation for complications of systemic therapy reported 11.1% of patients with breast cancer required hospital admission but this was not age-or stage-specific [18]. The results of our real-world study reflect good overall tolerability in the older population and are in keeping with the safety analysis from the PALOMAGE French study which showed palbociclib to be well-tolerated in this population with no new safety signals identified [9].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A more recent US study of the rates of hospitalisation for complications of systemic therapy reported 11.1% of patients with breast cancer required hospital admission but this was not age-or stage-specific [18]. The results of our real-world study reflect good overall tolerability in the older population and are in keeping with the safety analysis from the PALOMAGE French study which showed palbociclib to be well-tolerated in this population with no new safety signals identified [9].…”
Section: Discussionsupporting
confidence: 83%
“…Real-world studies have looked at the efficacy and safety of palbociclib, some of which focussed on the older patient group. A French real-world study of palbociclib in patients aged over 70 years (PALOMAGE) reported a lower incidence of grade 3/4 adverse events in those aged !80 years [9]. A US retrospective analysis included 92 patients aged !70 years treated with palbociclib and reported significantly higher rates of dose reductions and delays in patients !70, but with no detriment to survival outcomes [10].…”
mentioning
confidence: 99%
“…Recent real-world data analyses have shown that palbociclib is effective in patients with HR+/HER2– MBC in routine US clinical practice, but detailed information about the use of CDK4/6 inhibitors specifically in older patients is limited [ [8] , [9] , [10] , [11] , [12] ]. The available real-world studies including older European patients (≥70 or ≥75 years) support the effectiveness or tolerability of palbociclib in these age groups [ 13 , 14 ]. A better understanding of treatment benefits and risks in older women in the real-world setting in the United States is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Another meta-analysis of phase II and III studies also showed that palbociclib was associated with significantly increased rates of neutropenia in an older subgroup compared to their younger counterparts, with an ORR of 2.57. Leukopenia, anemia, back pain, asthenia, and infections were also more frequent in the older group [25] . Recently, results were reported from the French prospective study PALOMAGE and its safety analysis of palbociclib + ET in a real-life setting in women aged ≥ 70 years with HR+/HER2-ABC, where 807 patients were included with a median age of 79 years old.…”
Section: Discussionmentioning
confidence: 91%